Pendampingan Kompetisi Sains Menggunakan Pendekatan Islamic Contextual Teaching and Learning di MA Muwahidun - Prasetyo, Dody Rahayu (Mafapress Institut Pesantren Mathali'ul Falah Pati, 2023)
Rarely getting achievements in the field of physics in the Madrasah Science Competition (KSM) since 2018, is a problem experienced by Madrasah Aliyah (MA) Muwahidun. Through KSM assistance activities in the field of physics with the Islamic Contextual Teaching and Learning (ICTL) approach, it is hoped that students' competitive attitudes and ability to solve problems will increase. In addition, students are able to achieve the highest rankings. This activity is carried out in three stages, namely: preparation, implementation, and evaluation stages. The preparatory stage carried out includes 1) analyzing the grid, looking for Qur'anic verses related to physics, 3) compiling teaching materials and selection questions, and 4) analyzing the previous year's physics KSM questions. The implementation phase carried out includes 1) student selection, 2) guidance activities, 3) trial tests, and 4) district-level KSM tests. The final stage is carried out by evaluating the process of the beginning to the end of the activity. The results obtained that after the mentoring activities, namely 1) competitive attitude and 2) the ability to solve questions owned by students has increased. In addition, the results of the district-level physics KSM test ranked 1st. This is supported by students understanding the meaning of Qur'anic verses and Islamic applications about science obtained from the subjects of Al Burhan, History of Islamic Progress, Fiqih, Ushul Fiqih, and Adab.